Stable melt formation of 2D nitrile-based coordination polymer and hierarchical crystal-glass structuring - Das, Chinmoy; Ogawa, Tomohiro; Horike, Satoshi (Chemical communications (Cambridge, England), 2020)
Crystal melting and vitrification of nitrile-based two-dimensional coordination polymer (CP) were studied. The crystal melts at 169 °C and has a wide liquid-state temperature window of over 110 °C. The crystalline state transformed to a glassy state by melt-quench or mechanical milling. The mechanically induced glass showed permanent porosity, and it also showed glass-to-crystal transformation upon solvent treatment. Surface crystallization on top of the grain-boundary-free glass monolith was demonstrated. 2D nitrile-based coordination polymer crystal shows over 110 °C of windows of liquid state and it forms a glass monolith.